The Impact of the Digitalization in Uzbekistan’s Tourism to the Economy - Ashurova, Shakhnoza (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article we can see observation of the developing digital economy and its impact to Uzbekistan economy. Tourism is an information-rich field, in which the collection, transmission, analysis and storage of information play an important role in decision-making at all levels of the field. In this regard, the formation and development of the digital economy is of great importance for tourism activities, in which the latest information and communication technologies are actively used.